Investigation of circular economy practices in the context of emerging economies: a CoCoSo approach - Shahbaz Khan; Abid Haleem (International Journal of Sustainable Engineering, 2021)
Circular economy is gaining considerable attention among global business professionals, organisations, and academia. Industry and governments realise the fast depletion of resources & environmental degradation and a need for sustainable development. Despite this, there is a scarcity of literature related to the circular economy, the circular economy is effectively adopted through circular practices. Therefore, this study’s primary objective is to investigate the circular economy practices to transform an existing linear model into a circular economy model. In order to accomplish this objective, this research identified fifteen circular economy practices through the literature review and experts’ input. These circular economy practices are evaluated using CoCoSo and prioritised the circular economy practices based on their importance. Results show that the significant circular practice is ‘consumer awareness’, ‘legislation and policies’, ‘develop the circular culture’, ‘awareness among the supply chain partners’ and ‘designing products for circularity’. These are the practices that are essential to adopt for an organisation to adopt the circular economy effectively. This study facilitates managers to make an action plan for executing circular practices. By considering the prioritisation of circular practices, managers and professionals can optimise their organisational resources to adopt the circular practice effectively.